Congenital granular cell epulis in a neonate: a case report and review of diagnosis, treatment, and prognosis - Guidone, P. C.; Seccia, Roberta; Fabrocini, L. A.; Troiano, G.; Maffei, G.; Pedicillo, Maria Carmela; Pannone, Giuseppe; Lo Muzio, Lorenzo; Zamparese, Rosanna; Mori, Giorgio; De Stefano, Ilenia Sara (Frontiers in Oral Health, 2025)
Congenital granular cell epulis (CGCE) is a rare benign tumor typically presenting at birth and most commonly located on the maxillary alveolar ridge.Case PresentationWe report the case of a five-day-old female with a smooth, multilobulated mass on the right maxillary alveolar ridge causing feeding difficulties. Surgical excision was performed under sedation. Histological and immunohistochemical analysis confirmed the diagnosis of CGCE. No recurrence was observed at one-month follow-up.ConclusionEarly diagnosis and surgical treatment of CGCE are essential to avoid functional impairment. The prognosis is excellent following complete excision.